ALD TaN Barrier for Enhanced Performance with Low Contact Resistance for 14nm Technology Node Cu Interconnects. (10th September 2015) - Nag, Joyeeta; Cohen, Brian; Choi, Samuel; Ogino, Atsushi; Oh, Minseok; Yan, Yan; Liang, Jim; Christiansen, Cathryn; Kim, Andrew; Li, Baozhen; DeHaven, Patrick; Madan, Anita; et al.
Abstract : We report on an alternative atomic layer deposited (ALD) TaN barrier process for Cu interconnects for 14nm technology node and beyond. ALD films provide ultrathin, conformal barrier with reduced overhang and bottom thickness in contrast to physical vapor deposited (PVD) films. This enables via-contact resistance reduction and improved gap-fill while maximizing Cu volume in a trench/via structure. Blanket film studies show that ALD films are 10-15% less dense compared to Ta-rich PVD films, and more importantly only desired low-resistance a-Ta nucleates on ALD films vs. thin PVD films. To maximize density while protecting low-k dielectric during deposition and maintaining low-contact resistance, we explored different flavors and combinations of thermal (tALD) and plasma-enhanced ALD (PEALD). We achieved via contact resistance reduction of 25-35%, with equivalent or better performance for yield, defectivity and electromigration (EM), time-dependent dielectric breakdown (TDDB) and stress migration (SM) reliability.